Analisis Hubungan Antara Intensitas Membaca, Isi Buku Panduan Dan Relasi Pembaca Buku Panduan Terhadap Pemenuhan Kebutuhan Informasi Bagi Pegawai Museum Kepresidenan RI Balai Kirti - Helmidaffa, Juwita Qhalby; Saragi, Charles Parnauli (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
In an agency, institution or organization is very closely related to a media. Media published in an agency, institution or organization aims to be used as internal media that can be used by employees as a fulfillment of information needs. This study aims to examine employee exposure/reading intensity with the fulfillment of employee information needs at the Indonesian Presidential Museum Balai Kirti, to determine the contents of the museum manual with the fulfillment of employee information needs at the Indonesian Presidential Museum Balai Kirti, and to determine the relationship between museum manual readers and fulfillment of employee information needs at the RI Presidential Museum Balai Kirti. This study uses descriptive analysis techniques, validity tests, reliability tests and Rank Spearman correlation tests, with a census sample technique, the number of employees is divided into 19 civil servants, 8 PPNPN staff, and 4 apprentice students as educators at the Indonesian Presidential Museum Balai Kirti . The method of collecting data is through questionnaires (google form), interviews, field observations, and the theory of uses and gratification. The results of this study in the validity test showed valid results from each indicator contained in variable X and Y. In the reliability test, variable X and Y showed RELIABLE results. In the Spearman Rank correlation test, it shows a SIGNIFICANT result value and the correlation number has a positive relationship with a strong relationship. In the t test hypothesis test there is one result showing the independent variable (X2) which has no effect on the dependent variable (Y). Then the F test shows significant results simultaneously between the three independent variables (X1), (X2), and (X3) on the dependent variable (Y). The conclusion of this research is that the existence of this museum manual has an influence on fulfilling the information needs of employees at the Indonesian Presidential Museum, Balai Kirti. Keywords: Museum, Guidebook, Information